Risk Factors for Cardiovascular Disease and Their Clustering among Adults in Jilin (China) - Yu, Jianxing (Int J Environ Res Public Health, 2015)
Background: Clustering of cardiovascular disease (CVD) risk factors constitutes a major public health challenge. Although a number of researchers have investigated the CVD risk factor clusters in China, little is known about the related prevalence and clustering associated with demographics in Jilin Province in China; this study aims to reveal that relationship. Methods: A cross-sectional survey based on a sample of 16,834 adults aged 18 to 79 years was conducted in Jilin in 2012. The prevalence and clustering of CVD risk factors were analysed through complex weighted computation. Quantitative variables were compared by the t test, and categorical variables were compared by the Rao-Scott-χ(2) test. Finally, multivariable logistic regression analysis was used to evaluate the CVD risk factor clusters associated with demographics. Results: The prevalences of hypertension, diabetes, dyslipidemia, overweight and smoking were 37.3%, 8.2%, 36.8%, 47.3%, and 31.0%, respectively, and these risk factors were associated with gender, education level, age, occupation and family income (p < 0.05). Overall, compared with females, the adjusted ORs of ≥1, ≥2 and ≥3 risk factors clusters in males were 3.70 (95%CI 3.26 to 4.20), 4.66 (95%CI 4.09 to 5.31), and 5.76 (95%CI 5.01 to 6.63), respectively. In particular, the adjusted ORs of ≥1, ≥2 and ≥3 risk factors increased with age. Conclusions: CVD risk factor clusters are common among adults in northeast China, and they constitute a major public health challenge. More effective attention and interventions should be directed toward the elderly and toward persons with lower incomes and low levels of education.